Developments in the international distribution of income - Hans-Peter Nissen (Intereconomics, 1982)
The question of income distribution played a very important role in practical and theoretical development policy during the seventies. World market conditions were blamed for the fact that the income gap between industrialised countries and developing countries was widening. The demands to which this has given rise range from calls for “greater reliance on market forces”, “modification of the market form” and “greater market intervention” to insistence on the complete abolition of free market relationships. How has the relative income position of various groups of developing countries evolved in the last few decades?
Keywords: 330; World Income